Translational Cardiology Molecular Basis of Cardiac Metabolism, Cardiac Remodeling, Translational Therapies and Imaging Techniques (Molecular and Translational Medicine, 2012)
Translational Cardiology: Molecular Basis of Cardiac Metabolism, Cardiac Remodeling, Translational Therapies and Imaging Techniques provides an up-to-date introduction to the role circadian rhythms, cardiac plasticity, and mechanotransduction play in the heart, while at the same time introducing new developments in cellular, viral, and non-biologic therapies that are in the process of being developed. Importantly, the focus of this book is on topics that, due to their novelty, are largely not covered in the other major textbooks. A special emphasis is placed on the molecular basis of cardiac metabolism, new concepts in cardiac remodeling, and translational therapies and imaging techniques currently under development for clinical use. The chapters are written by experts from diverse clinical and biomedical research backgrounds. Translational Cardiology: Molecular Basis of Cardiac Metabolism, Cardiac Remodeling, Translational Therapies and Imaging Techniques simplifies the complexity of the molecular basis of disease by focusing on patient-oriented disease mechanisms and therapies and is of great value to a broad audience including physicians (e.g. cardiologists, cardiovascular surgeons, pathologists) as well as translational biomedical researchers in a wide range of disciplines